Rendang Jamur Tiram Sebagai Alternatif Usaha Olahan Jamur Tiram - Raden Rara Aulia Qonita; Nur Heriyadi Parnanto; Erlyna Wida Riptanti (Future Science, 2019)
Rendang is an authentic Indonesian food that is popular throughout the world. However, these foods contain high cholesterol so now we need to find alternative substitutes to make rendang. Oyster mushrooms have elasticity like beef so that they can be used as an alternative to making rendang. These kinds of businesses have good prospects to increase their business. High market demand and limited business competition have opened up huge market opportunities. This market opportunity must also be balanced with the quality and continuity of the product so that it can increase consumer confidence in the product of oyster mushroom rendang. Community empowerment carried out by the service team focuses on improving the quality of rendang products with marketable packaging. The result is that consumers begin to realize and like the oyster mushroom rendang and the oyster mushroom rendang market starting to target the upper-middle-class consumer segment.